2000
DOI: 10.1177/014107680009301205
|View full text |Cite
|
Sign up to set email alerts
|

Expectations and quality of life of cancer patients undergoing radiotherapy

Abstract: Expectations, real or false, affect the way patients respond to their illnesses. We assessed therapy-related expectations in relation to global quality of life in 55 cancer patients before and after radiotherapy. Factor analysis indicated that therapy-related expectations come into three broad categories--pain/emotional control, healing and tumour/symptom control. 35 patients expected 'healing' even though curative treatment was intended in only 19 and all patients had been fully informed. The expectation of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 35 publications
3
42
0
4
Order By: Relevance
“…The COMQ-12 is a patient-related outcomes questionnaire that is constructed to obtain information about the symptoms that are most important for the patient. It allows the clinician to get an idea of the expectations of patients regarding therapy and to choose an adequate management strategy that is consistent with these expectations [7] . We translated the original COMQ-12 into Dutch and tested it for validity, diagnostic accuracy, and test-retest reliability.…”
Section: Discussionmentioning
confidence: 99%
“…The COMQ-12 is a patient-related outcomes questionnaire that is constructed to obtain information about the symptoms that are most important for the patient. It allows the clinician to get an idea of the expectations of patients regarding therapy and to choose an adequate management strategy that is consistent with these expectations [7] . We translated the original COMQ-12 into Dutch and tested it for validity, diagnostic accuracy, and test-retest reliability.…”
Section: Discussionmentioning
confidence: 99%
“…Roscoe et al 261 examined treatment-related nausea in chemotherapy patients and reported, on the basis of two small studies, that there was a significant association between patients' pretreatment expectations of nausea and severity of nausea post chemotherapy. In Koller et al 's study 124 of expectations, quality of life and clinical variables with a sample of hospital inpatients receiving radiotherapy, quality of life was found to be altered little by radiotherapy but became substantially worse in the group who had expected healing but perceived that this had failed (even though physician-assessed Karnofsky performance status had not changed), although the authors do note that the exact temporal sequence of healing expectations and quality of life was not tested.…”
Section: Expectancy Itemsmentioning
confidence: 98%
“…Recently these classical endpoints in clinical trials were supplemented by new (hermeneutic) endpoints [1] like quality of life, expectations and negative affect as psychological basic variables self-reported by patients [2,3]. For this reason, the clinical scenario should be modelled as accurate as possible in animal trials including an equivalent of quality of life in animals.…”
Section: Introductionmentioning
confidence: 99%